دور يوليسيس آس. كرانت في الحرب الاهلية الأمريكية (1861-1865). - مطرود, علي خيري; صابون, فاطمة شيال (Journal of College of Education, 2018)
The civil war has become an important turning point in American history not only at the political and military levels but also at all other levels, especially social and economic ones, Because it redraws the American perception of many of the concepts that prevailed before, and the success of men who participated in the role played a major role in determining their fate and among those leaders General Ulysses. S. Grant, who is credited in many respects in resolving that war in favor of the North, And this is what the majority of the American people felt, so they were keen to be elected president of their country for two consecutive sessions to deal with the consequences of that war and the issue of reconstruction. In order to understand the nature of the American choice we must study the role of men in the American civil war. The research entitled "The Role of Ulysses in the American Civil War 1861-1865", and we have included a set of conclusions that we have reached in the light of our study of the facts presented to us in the research.